2023
DOI: 10.1158/1541-7786.mcr-22-0695
|View full text |Cite
|
Sign up to set email alerts
|

Targeting c-Jun Is a Potential Therapy for Luminal Breast Cancer Bone Metastasis

Abstract: Luminal breast cancer has the highest bone metastasis frequency among all breast cancer subtypes; however, its metastatic mechanism has not been elucidated because of a lack of appropriate models. We have previously developed useful bone metastatic cell lines of luminal breast cancer using MCF7 cells. In this study, we characterized bone metastatic MCF7-BM cell lines and identified c-Jun as a novel bone metastasis marker of luminal breast cancer. The protein level of c-Jun was upregulated in MCF7-BM cells comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…A study found that the protein c-Jun levels increased in MCF7-BM cells compared to the original cells ( 162 ). Additionally, the absence of c-Jun was observed to suppress tumor cell migration, transformation, and the ability to cause bone destruction (osteolysis).…”
Section: Available and Novel Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found that the protein c-Jun levels increased in MCF7-BM cells compared to the original cells ( 162 ). Additionally, the absence of c-Jun was observed to suppress tumor cell migration, transformation, and the ability to cause bone destruction (osteolysis).…”
Section: Available and Novel Therapiesmentioning
confidence: 99%
“…These insights open up promising avenues for the development of subtype-specific therapies that can effectively tackle bone metastasis in luminal breast cancer. By targeting c-Jun, researchers and clinicians may have the opportunity to provide more tailored and effective treatments for patients with this particular subtype of breast cancer, ultimately leading to improved outcomes and better quality of life ( 162 ).…”
Section: Available and Novel Therapiesmentioning
confidence: 99%